Noslēpuma neizpaušana - Vēverbrante, Madara (Latvijas Universitāte, 2008)
Bakalaura darbā „Noslēpuma neizpaušana” izpētīts, kas tiek definēts ar jēdzienu noslēpums un kā izpaužas noslēpuma izpaušana, tā traktējums Krimināllikumā, un šīs normas vēsturiskā attīstība. Izpētes gaitā apskatītas un izanalizētas ārvalstu tiesību normas, kuras regulē sveša noslēpuma neizpaušanas pienākumu personām, kurām klusēšana ir amata pienākums, un šīs normas salīdzinātas ar Latvijas Republikas tiesību normu.

The Bachelor Thesis „Secret’s unexposure” investigates what has been defined as a secret and what can be considered as disclosure of the secret and how is it interpreted in the Criminal Law and this rule historical development. During the investigation, rules of other countries dealing with the obligation of keeping other person’s secret as part of the profession have been viewed, analyzed and compared to the rules of Latvian Republic. Similarities and differences as well as compliance and compatibility of these rules and the article 145 of the Criminal Law have been examined.
Secret's unexposure
Keywords: Juridiskā zinātne